UNJUK KERJA KOMUNIKASI NIRKABEL HALF-DUPLEX ANTARKENDARAAN MEMANFAATKAN NRF24L01 - Amanda Saraswati, Ni Putu; Indra ER, Ngurah; Purnama, Fajar (Jurnal SPEKTRUM; Vol 11 No 1 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i01.p24, 2024)
This study investigates the efficacy of the affordable NRF24L01 wireless communication module in half-duplex mode for vehicle-to-vehicle (V2V) communication. The prototype integrated the NRF24L01 module with an ESP32 microcontroller and an OLED display. The study assesses the delay and packet success rate to uncover the module's attributes under half-duplex situations. This not only surpasses the mere collecting of data, but also emphasizes the practical limitations and strengths of the module. The project aims to achieve two main objectives: firstly, to gather empirical data that may be used to make well-informed decisions in the design of NRF24L01 applications, and secondly, to contribute to the broader examination of wireless communications protocols. It improves comprehension of the impact of half-duplex operation on the performance of the NRF24L01 module. By revealing the mechanics of half-duplex communication, it enhances the efficiency of NRF24L01 usage and facilitates the development of a better protocol.